The performance of a porous ceramic hydrostatic journal bearing - Durazo-Cardenas, Isidro; Corbett, John; Stephenson, David J. (Professional Engineering Publishing, 2010)
The performance of a porous-ceramic hydrostatic journal bearing manufactured by the starch consolidation (SC) technique has been examined using a highly instrumented test rig. The results have been compared with those of a 5-recess hydrostatic bearing of the same size and comparable design, under the same testing conditions. The SC porous-ceramic bearing showed an improved performance over the conventional hydrostatic bearing. Static and rotational stiffness were 95 per cent and over 150 per cent higher, respectively. In addition, the porous ceramic bearing exhibited a more economic performance with a 64 per cent lower flowrate and pumping power than the hydrostatic bearing. In terms of heat generation, the porous ceramic bearing showed 50 per cent lower temperature rise
Keywords: porous ceramic, starch consolidation, hydrostatic journal